THE EFFECT OF THE TAXATION SYSTEM, ACCOUNTABILITY AND EXAMINATION RISK TO THE TAXPAYER COMPLIANCE WITH TAXPAYER MORALE AS A MODERATING VARIABLE - Lilisen Lilisen; Vince Ratnawati; Novita Indrawati (PEKBIS, 2018)
The objective of this study is to investigate the effect of taxation system,accountability, examination risk on taxpayer compliance, and taxpayer morale as amoderating variable. The population are taxpayers registered as corporatetaxpayers in KPP Pratama Tampan Pekanbaru. The sampling technique usedpurposive sampling method which resulted sample of 99 respondents. We usedmultiple linear regression and moderated regression analysis for hypothesis testing.The results showed that accountability did not affect taxpayer compliance, whiletaxation system and examination risk have significant effect on taxpayer compliance.We also found that taxpayer morale moderates the effect of taxation system andexamination risk on taxpayer compliance. While taxpayer morale does not moderatethe effect of accountability on taxpayer compliance.